A Model of Engaging Teachers with the Prevention of Trafficking of Migrant Children: Case Study of Samut Sakhon, Thailand1 - Kranrattanasuit, Naparat; Sumarlan, Yanuar (Journal of Human Rights and Peace Studies, 2017)
Child labor exploitation in Samut Sakhon has been a perennial problem in Thailand. Migrant children’s public schools and learning centers have offered alternative educational thresholds to keep them in school longer to reduce child labor exploitation. However, these children tend to drop out of school early to become full-time laborers because of their families’ financial needs. This research presents a school-based anti-trafficking prevention program created through participatory action research in which elementary school teachers teach migrant students about the potential of migrant child exploitation. Through producing an Anti-Human Trafficking Handbook, this research raises awareness and knowledge to prevent the untoward exploitation. Previously, no other context-specific anti-human trafficking handbook co-produced by teachers and researchers exists. This research emphasizes a model that enhances serious collaboration of the teachers, students, and the research team to create an Anti-Child Trafficking Handbook with lessons and activities suited for their specific needs. The main contribution of this article to educational knowledge is the revelation of challenges that such prevention programs applicable to foreigners’ children might face from the state (policy), university (educational programs), or even among the educators themselves, both Thai or non-Thai.